Yevgenia Kovkina: THEORETICAL AND PRACTICAL ASPECTS OF STUDY OF THE COMMUNICATIVE ACT OF ADOPTION OF THE BENEFIT OFFER IN MODERN LINGUISTIC EXPERTISE OF SPEECH - Kovkina, Yevgenia (Linguistic Bulletin (Movoznavchyi Visnyk), 2022)
Аbstract. Introduction. Today in linguistic expertise it is important to establish in speech a communicative act of accepting a proposal of any benefit. These studies take place at the pragmatic level of discourse analysis in general. Purpose. The development of an algorithm for the study of the speech act of acceptance of the offer of benefits is one of the priority tasks of specialists in forensic linguistic expertise of speech. Results. One of the main roles in communication is played by communicative intention. The verbal act of acceptance (promises or promptings of any kind) is a pragmatic connection between utterances in a certain communicative situation. The speech act of acceptance of the offer of benefit is reflected in the speech act of consent, which according to the theory of speech acts belongs to the commissions. Functionally, the speech act of consent is a reaction to the previous part of the discourse (speech act, character). Responding to different types of initial illocutionary acts, the addressee uses the appropriate types of grammatical expression of the communicative act of acceptance (consent). Originality. The choice of the type of grammatical expression of the speech act of acceptance of the sentence is influenced by extra lingual factors. They depend on the specific discourse as a whole. On the basis of the conducted researches we allocate direct and indirect grammatical forms of the communicative act of acceptance of the offer of benefit. The direct grammatical form is used rarely. Direct consent is transmitted together with the commitment to perform certain actions. Much more difficult to study are communicative situations in which consent is expressed indirectly. Such consent uses various verbal and nonverbal methods. Among the answers that indicate the successful implementation of the perlocutionary act, affirmative sentences are used. At the verbal level, they do not have words with the meaning of acceptance of benefit, but convey conciliatory semantics. Conclusion. We distinguish the type of direct consent to the acceptance of a benefit offer and the type of agreement with the conditions, the choice of which is influenced by extra lingual factors of the communicative situation. In the analysis of discourse in general, a distinction should be made between direct and indirect forms of expression of the speech act of consent. Prospects for further research are seen in the deepening of the study of the communicative act, the allocation of other criteria for its analysis.